CHANGE MANAGEMENT IN INNOVATIVE ORGANIZATIONS: AN ANALYSIS OF THE DESIGN THINKING APPROACH - Ma. Yuzhen (Scholar Express Journals, 2025)
This paper explores the integration of Design Thinking (DT) as a strategic framework for managing change in innovative organizations. In an era marked by digital transformation, globalization, and evolving customer expectations, traditional change management models often fall short in fostering adaptability and creativity. Design Thinking, characterized by its human-centered, iterative, and problem-solving approach, offers a viable alternative for navigating complexity and driving organizational transformation. Through theoretical analysis, real-world examples, and literature synthesis, this paper examines how DT supports cultural adaptability, stakeholder engagement, and innovation in the face of change.
Keywords: Change Management; Design Thinking; Innovation